Access to Credit for Small Innovative Businesses. (15th May 2017) - dalla Pellegrina, Lucia; Frazzoni, Serena; Rotondi, Zeno; Vezzulli, Andrea
Abstract : Using data for a large sample of small firms collected through the 8th UniCredit Survey conducted in 2011, we investigate the extent to which banks of different size reward innovative firms, in terms of both access to lending and volume of credit granted. We find that more innovative firms are associated with weak credit rationing. Using instrumental variable techniques to manage the endogenous nature of innovation, we show that a large bank more strongly supports product innovation, whereas there is no substantial difference in the extent to which small and large banks provide credit to small firms undertaking process innovations.